Implementasi Sistem Pemerintahan Berbasis Elektronik (SPBE) dalam Layanan Izin Tinggal Kemigrasian Serta Tantangannya di Kantor Imigrasi Kelas I Khusus Non TPI Jakarta Selatan - Saraswati, Atika Ariyani; Hanita, Margaretha (Publikasi Indonesia, 2025)
The advancement of information technology compels governments to innovate in enhancing the quality of digital-based public services. One form of implementation of the Electronic-Based Government System (SPBE) is the immigration service transformation conducted by the Directorate General of Immigration through the launch of the Modul Lalu Lintas Orang Asing (Molina) application. This service enables applicants to submit stay permit applications online, streamlining and accelerating the service process. This study aims to analyze the implementation of SPBE in immigration stay permit services and identify emerging challenges. A qualitative descriptive method was used, with a case study at the South Jakarta Class I Non-TPI Immigration Office. The findings indicate that SPBE implementation through Molina has improved service efficiency and accessibility, but also presents new challenges, particularly in field monitoring and misuse of permits. The study concludes that successful digital transformation must be supported by adaptive control systems and stakeholder involvement. The implication is the need for strengthening institutional capacity and surveillance technologies to ensure the sustainability, accountability, and trustworthiness of digital public services.